2009
DOI: 10.1021/pr900570b
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of an Attenuated Francisella tularensis dsbA Mutant: Identification of Potential DsbA Substrate Proteins

Abstract: Francisella tularensis (F. tularensis) is highly infectious for humans via aerosol route and untreated infections with the highly virulent subsp. tularensis can be fatal. Our knowledge regarding key virulence determinants has increased recently but is still somewhat limited. Surface proteins are potential virulence factors and therapeutic targets, and in this study, we decided to target three genes encoding putative membrane lipoproteins in F. tularensis LVS. One of the genes encoded a protein with high homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(77 citation statements)
references
References 44 publications
9
67
0
1
Order By: Relevance
“…The goal of present study was to confirm the proposed FTS_1067 proteinprotein interactions reported previously [5] using either immunopurification of FLAG-tagged FTS_1067 protein from trans-complemented F. tularensis FSC200/ ΔFTS_1067 strain or the B2H systems and also to confirm whether these systems are suitable for this purpose.…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…The goal of present study was to confirm the proposed FTS_1067 proteinprotein interactions reported previously [5] using either immunopurification of FLAG-tagged FTS_1067 protein from trans-complemented F. tularensis FSC200/ ΔFTS_1067 strain or the B2H systems and also to confirm whether these systems are suitable for this purpose.…”
Section: Introductionsupporting
confidence: 51%
“…Unfortunately, the measurements of the β-galactosidase activity (Figure 2) did not prove the interaction of FTS_1067 with either of the two tested proteins. Similarly, all other proteins identified in the comparative proteome study [5] yielded negative results when assayed for the interactions as well (Pavkova and Schmidt, personal communications).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations